The International Baccalaureate and globalisation: implications for educational leadership - Gardner-McTaggart, Alexander Charles (2018)
This thesis offers a rare insight into senior leadership in International Baccalaureate (IB) international schools. The IB international school profits from the perceived quality and consistency of the IB brand, however, international schools suffer from an endemic culture of change and reinterpretation. The International Baccalaureate Learner Profile (IBLP) offers scope for consistency and an overarching ethos, and previous research suggests that ‘buy-in’ to the IBLP, and modelling of it in all aspects of school life, are essential in achieving this. The IB itself promotes the IBLP as a valuable tool for leadership. It emerges that buy-in to the IBLP in directors is split between the personal and the operational.